(untitled) - Strang, Gilbert (San Diego, 1988)
Contents: Matrices and gaussian elimination; The geometry of linear equations; An example of gaussian elimination; Matrix notation and matrix multiplication; Triangular factors and row exchanges; Inverses and transposes...
Keywords: Algebras, linear,Đại số tuyến tính